Increased Employee Productivity with The Application of e-HRM: Increased Employee Productivity with The Application of e-HRM (Case Studies at Pradita University) - Wijayadne, Devi rahnjen (International Business Management - Universitas Ciputra, 2021)
This research examines the role of e-HRM (electronic Human Resources Management) in improving employee productivity in higher education. The goal of this empirical study is to confirm and examine this e-HRM usage in higher education. Adaptive structuration theory (AST) is used, to understand the role of e-HRM in improving employee productivity. social factors and technological characteristics interact to affect group outcomes. AST argues that technology usage provides social structures to engage employees in social interaction that both enable and constrain human action within the firm. Research models are analyzed using linear regression and the result is indeed finding a positive effect of e-HRM usage on employee productivity that supports AST. E-HRM can help to streamline operational HRM activities; accelerate HR processes; improve communication between stakeholders include existed employees, potential employees, and management; reduce administrative tasks and HR staff headcount; and capture, create and transfer some HR knowledge more accurately and speedily for employee training and development. These advantages can help to increase employee productivity.